2018
DOI: 10.4110/in.2018.18.e38
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster DNA Vaccines with IL-7 and IL-33 Molecular Adjuvants Elicit Protective T Cell Immunity

Abstract: Herpes zoster (HZ), or shingles, is caused by the reactivation of latent varicella-zoster virus (VZV) from the sensory ganglia when VZV-specific T-cell immunity is decreased because of aging or immunosuppression. In the present study, we developed HZ DNA vaccine candidates encoding VZV proteins and cytokine adjuvants, such as IL-7 and IL-33. We immunized C57BL/6 mice with DNA plasmids encoding VZV glycoprotein E (gE), immediate early (IE) 63, or IE62 proteins and found that robust VZV protein-specific T-cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…DenV2 strains DJB2001 and D2S10 were propagated in a mosquito cell line C6/36 using DMEM supplemented with 2% FBS, penicillin (100 U/mL), and streptomycin (100 U/mL), concentrated by ultra‐centrifugation using sucrose‐gradient cushion, and titrated by focus‐forming assay. The recombinant vaccinia virus expressing CD8 + T‐cell epitope (OVA 257–264 , SIINFEKL) of chicken OVA (VVova 256–264 ) was obtained from Dr. Jonathan W. Yewdell (National Institutes of Health, Bethesda, MD, USA), and propagated in CV‐1 (American Type Culture Collection, Manassas, VA, USA, CCL70) cell line [74, 75]. HSV‐1 strains 17 and McKrae were propagated in Vero cells (American Type Culture Collection, Manassas, VA, USA, CCL81).…”
Section: Methodsmentioning
confidence: 99%
“…DenV2 strains DJB2001 and D2S10 were propagated in a mosquito cell line C6/36 using DMEM supplemented with 2% FBS, penicillin (100 U/mL), and streptomycin (100 U/mL), concentrated by ultra‐centrifugation using sucrose‐gradient cushion, and titrated by focus‐forming assay. The recombinant vaccinia virus expressing CD8 + T‐cell epitope (OVA 257–264 , SIINFEKL) of chicken OVA (VVova 256–264 ) was obtained from Dr. Jonathan W. Yewdell (National Institutes of Health, Bethesda, MD, USA), and propagated in CV‐1 (American Type Culture Collection, Manassas, VA, USA, CCL70) cell line [74, 75]. HSV‐1 strains 17 and McKrae were propagated in Vero cells (American Type Culture Collection, Manassas, VA, USA, CCL81).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also shown that IL-7 can not only enhance cellular immune responses, but also improves the humoral immune responses induced by vaccines (71,(148)(149)(150). As an adjuvant, IL-7 has been shown to stimulate antigen-specific CD4 + T cell, CD8 + T cell, and B cell responses to boost vaccine potency, as well as increasing the production of memory T and B cells to prolong the protective effects of vaccines (108,(151)(152)(153)(154) (Table 2).…”
Section: Il-7 Applications In Vaccinesmentioning
confidence: 99%
“…Also, administration of varicella vaccine generates VZV-speci ic humoral and cellular immune responses [304]. However, VZV-speci ic T-cell mediated immunity decreases with immunosuppression and advancing age [306,307]. Studies in older subjects have shown:…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…HZ-DNA vaccines with IL-7 and IL-33 molecular adjuvants strongly elicit protective T-cell immunity [306]. The magnitude of VZV-speci ic CD4+ T-cell response increases after VZV vaccination [314].…”
Section: T-lymphocytes: T-cell Mediated Immunity Consists Of Cd4 and mentioning
confidence: 99%
See 1 more Smart Citation